2017
DOI: 10.1016/j.schres.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in chemokine levels in schizophrenia and their clinical correlates

Abstract: Chemokines are promising biomarkers of immune activation and inflammation, but evidence for chemokine abnormalities in schizophrenia and their relationship to clinical factors remains inconclusive. We aimed to understand chemokine-related diagnostic differences and clinical correlates using a comprehensive panel and studying a large, well-characterized sample of adults with and without schizophrenia. We studied 134 outpatients with schizophrenia or schizoaffective disorder and 112 healthy comparison (HC) indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 68 publications
3
46
0
2
Order By: Relevance
“…Consistent with previous reviews and meta-analyses, 66,67 73% of these reports observed elevated levels of pro-inflammatory cytokines and chemokines in schizophrenia, including interleukin (IL)-6, 23,28,38,48 IL-1β, 38,57 tumor necrosis factor alpha (TNFα), 48 Eotaxin-1, 35,45 Eotaxin-2, 35 monocyte chemoattractant protein-1, macrophage inflammatory protein-1β, thymus-and activation-regulated chemokine, macrophage-derived chemokine, 45 and lower levels of the anti-inflammatory cytokine IL-2. 30 For TNF-α and IL-6, group differences were reduced and in some cases nonsignificant after controlling for potential confounds.…”
Section: Characteristics Of Reviewed Studiessupporting
confidence: 78%
See 2 more Smart Citations
“…Consistent with previous reviews and meta-analyses, 66,67 73% of these reports observed elevated levels of pro-inflammatory cytokines and chemokines in schizophrenia, including interleukin (IL)-6, 23,28,38,48 IL-1β, 38,57 tumor necrosis factor alpha (TNFα), 48 Eotaxin-1, 35,45 Eotaxin-2, 35 monocyte chemoattractant protein-1, macrophage inflammatory protein-1β, thymus-and activation-regulated chemokine, macrophage-derived chemokine, 45 and lower levels of the anti-inflammatory cytokine IL-2. 30 For TNF-α and IL-6, group differences were reduced and in some cases nonsignificant after controlling for potential confounds.…”
Section: Characteristics Of Reviewed Studiessupporting
confidence: 78%
“…57 Of the 11 articles, 3 reported effect sizes ranging from small to medium in size, for elevated levels in schizophrenia. 28,45,48 Other studies found no differences for C-reactive protein (CRP) 40 or intercellular adhesion molecule-1 (ICAM-1) 63 ; however, a more inclusive review and meta-analysis of all studies of CRP (without the specific study inclusion criteria that we used) has shown consistent elevations in CRP in schizophrenia. 68 Age Relationships Thirty-six percent of articles reported differential relationships between inflammation and age in schizophrenia and HCs.…”
Section: Characteristics Of Reviewed Studiesmentioning
confidence: 88%
See 1 more Smart Citation
“…These factors may be increased in schizophrenia compared to HCs (Emiliani et al, 2014;Muller et al, 2015;Shivakumar et al, 2014). This could, in theory, result in shortened LTL, but there is only mixed evidence that these factors are differentially prevalent in men vs women with schizophrenia (Joseph et al, 2015;Kunz et al, 2011;Lee et al, 2016;Ramsey et al, 2013;Reyazuddin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although we previously published data on high sensitivity C-reactive protein (hs-CRP) (Joseph et al, 2015), F2-isoprostanes (Lee et al, 2016), as well as cytokines (tumor necrosis factor-a (TNF-a), interleukin-6 (IL-6), and interferon-g (IFN-g) (Lee et al, In Press) and chemokines (Hong et al, In Press) in earlier subsets of this sample, the current report represents our first examination of LTL and its associations with demographic, psychiatric, and medical factors. The analyses were restricted to all participants who had LTL data available.…”
Section: Study Participantsmentioning
confidence: 99%